LEARNING TO READ THE QUR'AN IN PRIMARY EDUCATION INSTITUTIONS: A Case Study at SD Ummu Aiman and MIT Ar-Roihan Tangerang - Setyawan, Aris; Sukmana, Jaya (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: In Indonesia, the teaching of the Qur'an is a critical component of religious education, yet there are challenges in ensuring effective and meaningful instruction. Traditional methods often struggle to meet the evolving needs of students, highlighting the need for innovative approaches in Qur'anic education. Purpose: This study investigates the process of Qur'anic reading instruction at SD Ummu Aiman and MIT Ar-Roihan Tangerang, focusing on planning, implementation, and evaluation. Method: The research employs a qualitative descriptive method, utilizing data collection techniques such as in-depth interviews, field observations, and document analysis. Result: The findings reveal that both institutions use standardized learning methods, tailored to each school’s specific context. The planning process is divided into two levels: the basic level, which covers individual letter recognition and short phrases, and the advanced level, which includes Tajweed rules and the study of complex Qur'anic words. The implementation of teaching follows established lesson plans, with the evaluation process segmented into student evaluations and teacher assessments. Student evaluations are conducted daily and through a "Munaqosyah" system for level advancements, while teacher evaluations occur through scheduled mentoring sessions. Conclusion: This study concludes that Qur'anic reading instruction at both institutions is effective in promoting students' Qur'anic literacy, with a focus on understanding, correct pronunciation, and memorization. The research emphasizes the importance of adapting instructional methods to meet local needs and supports the integration of innovative teaching methods in Qur'anic education.